Taxonomic revision and phylogenetic analysis of the flatfish genus Trinectes (Pleuronectiformes: Achiridae) - Duplain, Rene R (University of Ottawa (Canada), 2009)
The taxonomic status of the 16 nominal species of the genus Trinectes (Pleuronectiformes: Achiridae) Rafinesque 1832 was revised based on a morphological study of 647 type and non-type specimens. Nine species were recognized as valid Trinectes inscriptus, T. maculatus, T. microphthalmus, and T. paulistanus are found in the Atlantic Ocean, from the Northern United States to Southern Brazil, whereas T. fimbriatus, T. fluviatilis, T. fonsecensis, T. opercularis, and T. xanthurus are found in the Pacific Ocean, from Mexico to Peru. An identification key to species is provided. The phylogenetic relationships of the species recognized were hypothesized based on a cladistic analysis of 22 morphological, meristic, and osteological characters. The analysis resulted in one most parsimonious tree with a length of 39 steps (CI = 0.69; RI = 0.79). The tree showed that Trinectes is monophyletic on the basis of two synapomorphies: an unpierced interbranchial septum, and seven to nine pterygiophores anterior to the neural spine of the third precaudal vertebra. Trinectes inscriptus is the most plesiomorphic species of the genus, and all other species form a monophyletic group subdivided into two clades. The first contains (from most plesiomorphic to recent): T. paulistanus, T. fonsecensis, and the T. fluviatilis-T. xanthurus clade. The second clade includes (from most plesiomorphic to recent): T. maculatus, T. opercularis, and the T. fimbriatus- T. microphthalmus clade. The resulting cladogram depicts a sequence of speciation events and provides an opportunity to propose a biogeographical hypothesis on the evolution of Trinectes.
Keywords: Biology, Evolution and Development.